A new photoactivable NO‐releasing {Ru−NO}6 ruthenium nitrosyl complex with a tetradentate ligand containing aniline and pyridine moieties. Issue 2 (18th December 2021) - Cho, Jang‐Hoon; Kim, Minyoung; You, Youngmin; Lee, Hong‐In
Abstract: A new type of photoactivable NO‐releasing ruthenium nitrosyl complex, [Ru(EPBP)Cl(NO)], with a tetradentate ligand, N, N' ‐(ethane‐1, 2‐diyldi‐ o ‐phenylene)‐bis(pyridine‐2‐carboxamide) (= H2 EPBP) was synthesized. Single crystal X‐ray crystallography revealed that the complex has a distorted octahedral coordination geometry and NO is positioned at cis to Cl − ion. NO‐photolysis was observed under a white room light. The photodissociation of Ru−NO bond was identified by various techniques including X‐ray crystallography, IR, UV/Vis absorption, electron paramagnetic resonance (EPR), and NMR spectroscopies. Quantum yields for the NO‐photolysis of the complex in CH3 OH, CHCl3, DMSO, CH3 CN, and CH3 NO2 were measured to be 0.19–0.36 with 400 (±5) nm excitation. Density functional theory (DFT) and time‐dependent density functional theory (TDDFT) calculations were performed to understand the details of the photodissociation of the complex. The calculations suggest that the NO photolysis is most likely initiated by the electronic transition from the aniline moiety π MOs ( π (aniline)) of the EPBP 2− chelating ligand to the π‐antibonding MO of Ru−NO ( π *(Ru−NO)). Experimental and theoretical investigations indicate that the EPBP 2− ligand provides an effective platform forming ruthenium nitrosyl complexes useful for NO‐photoreleasing. Abstract : A new type of photoactivable NO‐releasing ruthenium nitrosyl complex with a tetradentate ligand (EPBP 2− ) is developed. Quantum yields for the NO‐photolysis of the complex is measured to be 0.19–0.36 when the complex was photoirradiated with 400 nm. Experimental and theoretical investigations indicate that the EPBP 2− ligand provides an effective platform forming RuNO complexes useful for NO‐photoreleasing.